Adenopygus: A new genus and two new species of Luzarinae cricket of Brazilian Atlantic Forest (Orthoptera: Grylloidea) - Bolfarini, Marcio P. [UNESP]; De Mello, Francisco De A. G. [UNESP] (Magnolia Press, 2012)
The aim of the present work is to describe Adenopygus, a new genus with two species of luzarine phalangopsid crickets from the Atlantic Forest on the Mantiqueira fault escarpment of southeastern Brazil. Copyright © 2012 Magnolia Press.
Keywords: Description; Grylloidea; New taxa; Orthoptera; Phalangopsidae